Effects of Grit on the Academic Success of Adult Female Students at Korean Open University. Issue 4 (August 2018) - Hwang, Mae Hyang; Lim, Hyo Jin; Ha, Hye Suk
This study examined the structural relationship between age, grit (i.e., perseverance of effort and consistency of interest), conscientiousness, self-control, and school success of female students at an Open University in Korea. We analyzed 509 students' responses, and it turned out that the level of perseverance of effort was negatively correlated with academic maladjustment. Also, perseverance of effort had a positive indirect effect on grade point average scores. Conscientiousness and self-control were found to be positively correlated with grit factors and they had negative effects on academic maladjustment through perseverance of effort. Age had both direct and indirect effects on grit and academic success of the students.